Portraits de migrants irlandais pendant la Grande Famine (1845-1852) - Géraldine Vaughan (Revue Française de Civilisation Britannique)
Irish emigration was a reality well before the Great Famine, but it changed significantly after 1845, with more young women and entire families crossing the Atlantic or the Irish Sea. Despite official proposals to assist emigration, it was largely financed by the migrants themselves or their families, and they moved to the United States and Britain rather than to the colonies, with the exception of Canada. The influx of Irish migrants often triggered hostile reactions in America and Great Britain, where anti-Catholic movements emerged.